Early morden Vietnamese Painting : Hội họa Việt Nam hiện đại thuở ban đầu / Lady Borton, Hữu Ngọc - Lady. Borton
Culture schoplar Huu Ngoc and American writer Lady borton have brought us the first series of bilinggual handbooks on Vietnamese culture. These books are suitable for Vietnamese studying English and for foreigners studying Vietnamese.